2018
DOI: 10.2478/fhort-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of coupling gamma irradiation with calcium chloride and lemongrass oil in maintaining guava fruit quality and inhibiting fungal growth during cold storage

Abstract: This study was performed to explore the efficacy of combining more than one postharvest treatment in maintaining some quality attributes and reducing fungal pathogenicity in cold-stored guava fruits. The investigated postharvest treatments included the control, CaCl 2 (4%), lemongrass oil (2 dm 3 kg -1 ), gamma (γ) irradiation (0.2, 0.4 and 0.6 kGy), 0.4 kGy γ irradiation + CaCl 2 (4%), and 0.4 kGy γ irradiation + lemongrass oil (2 dm 3 kg -1 ). The studied physiochemical attributes included weight loss, decay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
3
4
0
Order By: Relevance
“…It was reported that Ca applications strengthen the cell wall and membrane structure, making the fruit more resistant to fungal activity (Wang and Long, 2015). Similarly, in some previous studies, conducted in peach (Salem et al, 2016) and kiwifruit (Hassanein et al, 2018), Ca treatments also reduced deterioration during storage.…”
Section: Resultssupporting
confidence: 74%
“…It was reported that Ca applications strengthen the cell wall and membrane structure, making the fruit more resistant to fungal activity (Wang and Long, 2015). Similarly, in some previous studies, conducted in peach (Salem et al, 2016) and kiwifruit (Hassanein et al, 2018), Ca treatments also reduced deterioration during storage.…”
Section: Resultssupporting
confidence: 74%
“…Previous studies reported that the use of edible coatings [10][11][12] propolis [13], chitosan [14], plants extract or essential oils [15][16][17][18][19] calcium salts [20,21] provides successful control of postharvest fruit decay and improves the storability of fruits. Apart from this, postharvest heat treatment has also reported to provide effective control of postharvest decay and prevent quality loss in storage rooms [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Fruits were stored for 60 days and fruit quality analysis was performed with 20 days interval (20,40 and 60 days of storage). At the mentioned days, 10 fruits from each of the above mentioned treatment were taken out from the storage room and the following quality parameters were measured.…”
Section: Fruit Quality Analysismentioning
confidence: 99%
“…However, there is an increasing public concern about the use of fungicides which increased the need for controlling postharvest decay in environmentally friendly methods [4,9]. Previous studies reported that the use of edible coatings [10][11][12] propolis [13], chitosan [14], plants extract or essential oils [15][16][17][18][19] calcium salts [20,21] provides successful control of postharvest fruit decay and improves the storability of fruits. Apart from this, postharvest heat treatment has also reported to provide effective control of postharvest decay and prevent quality loss in storage rooms [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%